PENGEMBANGAN ALAT PERAGA GEOMETRI 3D MELALUI ALGEDRA UNTUK MEMFASILITASI KECERDASAN SPASIAL - Sabil Ibadurrohman, Muhammad; Muhamad Maulana, Rendy; Maulana Muslim, Farhan (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
The development of technology in this world is growing rapidly. Today, development of technology has penetrated and developed considerably, especially in the education sector such as the use of google sites, Geogebra, etc. which can be used as learning media, especially in the field of mathematics. However, this technology-based learning media only places students as passive elements in the learning process. The passive element in question is the lack of spatial reasoning ability of students in understanding learning materials, one of which is Space Geometry material in mathematics subjects. To create teaching and learning that is easy to understand in order to improve spatial abilities, it is necessary to have props that can visualize space buildings so that students can better describe the space buildings being studied. AR-based technology can be a solution to improve students' spatial reasoning because AR is an interactive media and has visualization capabilities. The application of technological aids like AR, if properly utilized, will be a great way to counter students' passivity. Learning mathematics using Augmented Reality technology innovation could simplify learners in understanding the material, especially in geometry material. Based on this, we developed teaching aids on three-dimensional building materials.